MCQ Generator using Ontological Approach / Nurul Diyana Mohd Nor - Mohd Nor, Nurul Diyana (2020)
Educational systems today need an effective method to evaluate students in a competent way on their major concepts learned from their studies. The preparation of a set of questions will take time for lecturers and may not be applicable to material learned by the students if questions are raised from external sources such as text books or questions bank. Multiple Choice Question (MCQ) question generator is a system that generate the question automatically based on ontology of Operating System subject only. Students learn how to formulate and answer questions about situations, facts and ideas while trying to understand the text. This system basically can reduce the time consumption for the lecturers. Rule-based is the main technique to generate the question and answer selection for each question for this system. This MCQ question generation system is gives a lot of benefit for the lecturers. This question generation system using Waterfall Model and the system testing is conducted using functional testing and validation testing. The validation result is tested by using the ontology of Operating System. As this system is completed, it can generate and list the question related to ontology of Operating System for the lecturers.